Architected Materials: Multistable Shape‐Reconfigurable Architected Materials (Adv. Mater. 36/2016). Issue 36 (September 2016) - Haghpanah, Babak; Salari‐Sharif, Ladan; Pourrajab, Peyman; Hopkins, Jonathan; Valdevit, Lorenzo
Abstract : On page 7915, L. Valvedit and co‐workers report multi‐stable shape‐reconfigurable architected materials encompassing a living hinge, which enable exceptional combinations of high strength, high volumetric change, and complex shape‐morphing patterns. These properties could pave the way for the manufacturing of highly adaptable components that are fully reconfigurable based on functionality. Other foreseeable applications include deployable structures, multi‐purpose structures, and structures for energy absorption, vibration control, and tunable phononic response.